Lite marketing: consumer attitude and market response. (24th August 2011) - Chaudhary, Richa; Aggarwal, Artee; Gopal, R.
This study aims to explore the attitude and preference of Indian consumers towards latest concept and technology of 'lite marketing' and forecast the future of these 'lite/low calorie' products in Indian market. The study is descriptive in nature and to achieve its objective advanced SPSS statistical software, version 16 is used. The analysis indicates that Indian consumers are now well aware of the 'wealth of health' and want to stay healthy and in shape. The study found that majority of customers feel that 'lite' products are a healthy way to stay in shape and there is huge growth potential for lite products in the Indian market. The findings of the study provide opportunity to marketers to better understand the changing food consumption pattern of Indian consumer. The paper provides useful information on the concept of 'lite' marketing i.e., marketing of 'lite'/low calorie food product, which is in its nascent stage.